The Influence Of Learning Motivation And Learning Models On Training Participants Competence At The Boyolali Job Training Center - Sari, Rosyana Denni Purnama; Cahyani, Rusnandari Retno; Mutiasari, Annisa Indah (UNIVED Press, 2026)
This study aims to analyze the effect of learning motivation and learning models on the competence of training participants in the Office Administration Program at the Boyolali Job Training Center (BLK). The research employs a quantitative descriptive approach with a total sample of 96 participants who completed the training from 2022 to 2024. Data were collected using questionnaires and analyzed using multiple linear regression. The results show that learning motivation has a positive and significant effect on participants' competence (p = 0.000), while the learning model does not have a statistically significant effect (p = 0.410). Simultaneously, both variables significantly influence participants' competence (p = 0.000) with a determination coefficient (R²) of 0.208. This implies that 20.8% of competence variation can be explained by the two independent variables.